Características de utilización de medicamentos antiepilépticos en el servicio de salud mental–I del hospital nacional Edgardo Rebagliati Martins, enero – junio del 2015” - Romero Vásquez, Sara Melissa (2017)
The present study evaluated the characteristics of antiepileptic drug use in the Mental Health-Hospitalization I Service of the Edgardo Rebagliati Martins-EsSalud National Hospital, between January and June of 2015. A descriptive, cross-sectional and retrospective study of the use of These drugs, which included patients hospitalized in the Women's Mental Health Service (SM-I). The Daily Definite Dose System (DDD) was used as the unit of measurement for 100 bed-days, in addition to consumption expenditure Included in this period. Noting that the drug with the highest DDD is valproic acid 34,05 DDD/100 bed-days, followed by clonazepam 22,67 DDD/100 bed-days, carbamazepine 12,89 DDD/100 bed-days, while the drug Lower DDD is lamotrigine 0,81 DDD/100 bed-days. Also the drugs with the highest absolute expense in this service were valproic acid 80,25%, followed by topiramate 8,06% and carbamazepine 3,80%. From the results obtained, it is concluded that the most commonly used antiepileptic drug is valproic acid 34,05 DDD/100 bed-days; This drug being the highest-cost antiepileptic drug with a value of 80,25% of the total expenditure in the study period equivalent to 5166,4 soles.